2015
DOI: 10.3354/meps11141
|View full text |Cite
|
Sign up to set email alerts
|

Visual and behavioral evidence indicates active hunting by sperm whales

Abstract: It is hypothesized that sperm whales employ active pursuit strategies for hunting prey, mainly deep-sea squid at great depths, but no visual evidence has been obtained to confirm this. We recorded the hunting behavior of sperm whales using animal-borne cameras and accelerometers simultaneously deployed on 17 whales, and obtained 42.8 h of diving data, including 17 715 images. A statistical comparison indicated no clear effect of light (with or without flashing white lights from cameras) on diving behavior of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In the last decades, the development of new tools to study the sounds and movements of free-ranging echolocating whales has extended our knowledge about sound production in sperm whales 21 22 40 41 , the acoustic properties of their clicks 23 42 43 , their echolocation behaviour 44 45 46 47 48 and movements during foraging 14 15 16 29 49 . However, information about how the largest tooth-bearing predator in the world tracks and captures small and agile prey is still scarce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decades, the development of new tools to study the sounds and movements of free-ranging echolocating whales has extended our knowledge about sound production in sperm whales 21 22 40 41 , the acoustic properties of their clicks 23 42 43 , their echolocation behaviour 44 45 46 47 48 and movements during foraging 14 15 16 29 49 . However, information about how the largest tooth-bearing predator in the world tracks and captures small and agile prey is still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Aoki et al . 16 have further shown that such speed bursts are associated with squid ink and body parts passing cameras placed on the back of tagged sperm whales. These results show that sperm whales actively pursue prey during foraging dives.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Although little is known about the swimming kinematics of deep-diving toothed whales, the diving behaviour of several species such as sperm whales, beaked whales, pilot whales and northern bottlenose whales has been investigated in detail by using animal-borne recorders (e.g. Amano and Yoshioka, 2003;Miller et al, 2004b;Tyack et al, 2006;Watwood et al, 2006;Aoki et al, 2007Aoki et al, , 2012Aoki et al, , 2015Aguilar Soto et al, 2008). Sperm whales routinely dive to depths of 400-1300 m for half an hour or longer (Amano and Yoshioka, 2003;Miller et al, 2004b;Watwood et al, 2006;Aoki et al, 2007).…”
Section: Comparison Of Transit Speed and Dive Duration Among Deepdivimentioning
confidence: 99%
“…, Aoki et al . ). With minimal direct observations, vertical profiles of time spent at different depth and/or temperature strata in the water column can provide useful information to deduce differences in dive strategy and habitat use between species and sexes, as well as over diurnal cycles (Johnson et al .…”
mentioning
confidence: 97%